2015
DOI: 10.1038/srep09717
|View full text |Cite
|
Sign up to set email alerts
|

Light interaction in sapphire/MgF2/Al triple-layer omnidirectional reflectors in AlGaN-based near ultraviolet light-emitting diodes

Abstract: This study examined systematically the mechanism of light interaction in the sapphire/MgF2/Al triple-layer omnidirectional reflectors (ODR) and its effects on the light output power in near ultraviolet light emitting diodes (NUV-LEDs) with the ODR. The light output power of NUV-LEDs with the triple-layer ODR structure increased with decreasing surface roughness of the sapphire backside in the ODR. Theoretical modeling of the roughened surface suggests that the dependence of the reflectance of the triple-layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this way, high reflectivities have been reported for all angles of incidence in the visible range for an ODR formed by a semiconductor, a quarter-wavelength transparent dielectric layer and a metal [9]. More recently, Lee et al [10] obtained a high reflectance over the ultraviolet (300-500 nm) in a sapphire MgF Al 2 triple-layer and Liu et al [11] described average reflectances exceeding 98% from 1.261 to 1.533 μm with reflectors made from all-dielectric metamaterials. On the other hand, Moitra et al [12,13] demonstrated an average reflectance over 98% across a 200 nm wide bandwidth in the infrared region for a silicon metamaterial monolayer, while Slovick et al [14] developed a 0.45 μm thick, silicon-based metamaterial monolayer with normal-incidence reflectivity over 99.999% at 1.5 μm.…”
Section: Introductionmentioning
confidence: 82%
“…In this way, high reflectivities have been reported for all angles of incidence in the visible range for an ODR formed by a semiconductor, a quarter-wavelength transparent dielectric layer and a metal [9]. More recently, Lee et al [10] obtained a high reflectance over the ultraviolet (300-500 nm) in a sapphire MgF Al 2 triple-layer and Liu et al [11] described average reflectances exceeding 98% from 1.261 to 1.533 μm with reflectors made from all-dielectric metamaterials. On the other hand, Moitra et al [12,13] demonstrated an average reflectance over 98% across a 200 nm wide bandwidth in the infrared region for a silicon metamaterial monolayer, while Slovick et al [14] developed a 0.45 μm thick, silicon-based metamaterial monolayer with normal-incidence reflectivity over 99.999% at 1.5 μm.…”
Section: Introductionmentioning
confidence: 82%
“…An ODR structure comprised of pGaN, SiO 2 and metal Al is fixed on the bottom of the model to reflect photon and make light mainly extracted from the transparent sapphire. Al-based reflector is a good alternative for NUV LEDs because of the high reflectivity in the UV wavelength range [15], [16], [19]. The thicknesses of the nGaN and the sapphire are set to 3 μm and 1 μm, respectively.…”
Section: Calculation Of Lee With 3d Fdtd Methodsmentioning
confidence: 99%
“…To enhance the LOP of GaN-based LEDs, a variety of structures with microscale and/or nanoscale features have been incorporated into LEDs. Such features include photonic crystals, conductive omnidirectional reflectors, , microlens arrays, plasmonic nanostructure, nanorods, ,, and surface roughening of current spreading layer. , They have been demonstrated to enhance the device performance largely by overcoming TIRs. Most studies have been focused on surface texturing of micrometer size due to the ease of fabrication, among which transparent electrode texturing and patterning is one of the commonly used effective methods.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the LOP of GaN-based LEDs, a variety of structures with microscale and/or nanoscale features have been incorporated into LEDs. Such features include photonic crystals, 8−11 conductive omnidirectional reflectors, 12,13 microlens arrays, 14−16 plasmonic nanostructure, 17−19 nanorods, 6,20,21 and surface roughening of current spreading layer. 22,23 They have been demonstrated to enhance the device performance largely by overcoming TIRs.…”
Section: Introductionmentioning
confidence: 99%